Maternal and perinatal outcome in patients with preterm labor pains receiving tocolytic therapy - Rajpal, Tanya; Patil, Pooja; Sharma, Priyanka; Mitra, Nishi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The objective of this study was to assess the maternal and neonatal outcomes in patients with preterm labor pains and also to correlate threatened abortion with preterm pains. Methods: The study conducted was a prospective observational study. 100 cases of preterm labor admitted to JK hospital, Bhopal over a period of 2 years with singleton gestation between 28 to 36+6 weeks were included. Results: Maximum preterm deliveries were in the late preterm group (80%). Correlation of preterm labor with threatened abortion was not significant (OR=1.03; p>0.05). 42% cases delivered vaginally and 58% by LSCS. Prolongation of pregnancy after tocolytic therapy was upto 12 hours in 35% cases, 12-24 hours in 40% cases and >24 hours in only 15% cases. The most commonly encountered neonatal complication was RDS, 37%, out of which 9% required resuscitation at birth and 8% required ventilator support followed by jaundice in 23%, sepsis in 3% cases and NEC in 4% cases. The association between gestational age and requirement of resuscitation at birth (X2=19.9; p=0.00), need of ventilator (X2=12.6; p=0.002) and neonatal RDS (X2=6.9; p=0.031) was found to be significant. Conclusions: Preterm births are major obstetric problem that have an extensive impact on neonatal morbidity and mortality.